DOCKING STUDIES IN TARGET PROTEINS INVOLVED IN ANTIBACTERIAL ACTION MECHANISMS: ALKALOIDS ISOLATED FROM SCUTELLARIA GENUS - R, Sri Dharani; R, Ranjitha; R, Sripathi; K S, Ali Muhammad; S, Ravi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: In the present work, docking study was performed for 22 selected alkaloids isolated from the genus Scutellaria to evaluate their affinity to bacterial proteins that are known targets for many antibiotics with a different mechanism of action: Inhibitors of cell wall synthesis, inhibitors of nucleic acids synthesis and antimetabolites. Methods: Molecular docking study was carried out using AutoDock 4.2 version and the visualization result using Chimera 1.10 and Discovery Studio 4.5. Result: Among the 22 alkaloids studied, with the DNA gyrase protein 1KZN and a dihydropteroate synthase enzyme 3TYE, the compound scutebarbatine E showed a docking score of −8.5 and −8.7 Kcal/mol, respectively, involving with hydrophilic and hydrophobic interactions. With respect to MurD ligase involved in cell wall synthesis 1UAG and 2X5O, the compound 6,7,nicotinyl scutebarbatine G fared well with a docking score of −10.1 and −10.2 Kcal/mol, respectively. Scutebarbatine G performed well with respect to 3UDI with binding scores of −9.3 K cal/mol. Conclusion: Overall, it seems that for the selected alkaloids from the genus Scutellaria, the main mechanism of the action is the inhibition of cell wall synthesis. Keywords: Scutebarbatine, Alkaloids, Molecular docking, Antimicrobial studies.